The Role of Self-Compassion on Muslim Students’ Altruistic Behavior during COVID-19 Pandemic - Dwimahesi, Narulita Natasya; Musthofa, Wakhid (Jurnal Psikologi Integratif, 2023)
Large-Scale Social Restrictions in Indonesia during the COVID-19 pandemic caused a lack of social contact, thereby limiting individuals from providing direct assistance to others. Conversely, someone who has self-compassion is indicated to have good altruistic behavior. The present study aims to investigate the correlation between self-compassion and altruistic behavior among students during the Large-Scale Social Restrictions in Indonesia caused by the COVID-19 pandemic. This research employed an incidental sampling technique, with 400 college students. The participants comprised 76 men and 324 women, aged between 18 and 25 years. The study utilized the altruism scale (20 items; = 0.867) and the self-compassion scale (23 items; = 0.892) to measure self-compassion and altruistic behavior, respectively. The Spearman rank correlation technique was employed to test the hypothesis, which resulted in a correlation coefficient of 0.254 with p = 0.001 (p < 0.05). The research findings indicate a positive and significant relationship between self-compassion and altruism among students during the pandemic. Specifically, the higher the level of self-compassion, the higher the altruistic behavior. These results suggest that fostering self-compassion in individuals may lead to greater social benefits, such as encouraging positive social habits. Pembatasan Sosial Berskala Besar di Indonesia pada masa pandemi COVID-19 menyebabkan kurangnya kontak sosial sehingga membatasi individu untuk memberikan bantuan langsung kepada orang lain. Di sisi lain, seseorang yang memiliki self-compassion digambarkan dapat memiliki perilaku altruisme yang baik. Penelitian ini bertujuan untuk mengetahui hubungan antara self-compassion dengan perilaku altruisme pada mahasiswa di masa pandemi COVID-19. Penelitian ini menggunakan insidental sampling dengan responden sejumlah 400 mahasiswa. Instrumen yang digunakan adalah skala altruisme (α= 0,867) dan skala self-compassion (α= 0,892). Uji hipotesis menggunakan teknik korelasi rank spearman menunjukkan koefisien korelasi sebesar 0,254 dengan p = 0,000 (p < 0,05). Hasil penelitian menunjukkan bahwa terdapat hubungan yang positif dan signifikan antara self-compassion dengan perilaku altruisme pada mahasiswa di masa pandemi COVID-19. Semakin tinggi self-compassion maka semakin tinggi pula perilaku altruisme. Implikasi dari penelitian ini adalah individu dapat memiliki kesadaran self-compassion yang baik sehingga dapat bermanfaat lebih luas bagi masyarakat mengenai kebiasaan sosial yang positif.